2015
DOI: 10.1021/jacs.5b03732
|View full text |Cite
|
Sign up to set email alerts
|

An Umpolung Approach to Alkene Carboamination: Palladium Catalyzed 1,2-Amino-Acylation, -Carboxylation, -Arylation, -Vinylation, and -Alkynylation

Abstract: Conventional approaches to Pd-catalyzed alkene 1,2-carboamination rely upon the combination of a nucleophilic nitrogen-based component and an internal C-based or external oxidant. In this study, we outline an umpolung approach, which is triggered by oxidative initiation at an electrophilic N-based component and employs "standard" organometallic nucleophiles to introduce the new carbon-based fragment. Specifically, oxidative addition of a Pd(0)-catalyst into the N-O bond of O-pentafluorobenzoyl oxime esters gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(95 citation statements)
references
References 47 publications
3
91
0
1
Order By: Relevance
“…For Conditions A, fast protodecarboxylation of the pentafluorobenzoate leaving group to afford pentafluorobenzene regenerates the base (K 2 HPO 4 ) and allows catalytic quantities of this component to be used. We have confirmed the formation of pentafluorobenzene by GCMS analysis of crude reaction mixtures, and our previous studies have shown that the protodecarboxylation process is facile 21. Under both Conditions A and B, minimal conversions are observed in the absence of base and hindered organic variants (e.g.…”
supporting
confidence: 83%
“…For Conditions A, fast protodecarboxylation of the pentafluorobenzoate leaving group to afford pentafluorobenzene regenerates the base (K 2 HPO 4 ) and allows catalytic quantities of this component to be used. We have confirmed the formation of pentafluorobenzene by GCMS analysis of crude reaction mixtures, and our previous studies have shown that the protodecarboxylation process is facile 21. Under both Conditions A and B, minimal conversions are observed in the absence of base and hindered organic variants (e.g.…”
supporting
confidence: 83%
“…It was found that trialkylammonium pentafluorobenzoates undergo facile protodecarboxylation (Scheme 35, top). [45] The formation of C 6 F 5 H was observed by 1 H and 19 F NMR in aza-Heck cyclizations, which confirms that decarboxylation occurs during catalysis. Bower suggested that decarboxylation process enforces access to cationic intermediate 10 , which, in turn, accelerates pendant alkene ligation and C-N bond formation (Scheme 35, bottom).…”
Section: Aza-heckmentioning
confidence: 67%
“…[45] Mechanistic investigations showed that the pentafluorobenzoate leaving group is very important for the efficiency of reported protocol, as it undergoes self-clearance from the reaction system by facile protodecarboxylation.…”
Section: Aza-heckmentioning
confidence: 99%
“…3)3132333435363738394041424344454647484950515253545556575859606162636465666768. Coordination of the nitrogen atom in MeCN 2a with AgCO 3 gives the intermediate A , which sequentially reacts with AgCO 3 to afford the AgCH 2 CN intermediate B and AgHCO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the major synthetic targets for such transformations, including diamination789101112131415, aminooxygenation161718192021222324, aminohalogenation252627282930 and carboamination313233343536, is the incorporation of a nitrogen atom (amino, amide or azide groups) across the C–C double bonds to build useful N -containing molecules through the formation of a C–N bond. Despite significant progress in the field, approaches of the alkene carboamination for producing linear N -containing molecules are scarce and remain a great challenge (Fig.…”
mentioning
confidence: 99%